PROVING INTO URBAN LINKAGE THEORY: THE CASE OF INDIA STREET, KUCHING, SARAWAK - Julaihi, Wahid; Azli, Abdullah; Bassim, Salleh; Bambang, Karsono (Academia Industry Networks, 2021)
The life of the people on the street is governed by the users who are strangers in general. The activities are the central medium that makes the street alive. This simple paper advancing the urban design theory that has been tested and criticized elsewhere. The main figures like Jacobs, Whyte, Seamon and Gehl have used the western plaza and streets to evaluate the success and failure of cities gauging the same theory. With a similar approach, the far-flung India Street of Kuching is examined via its linkage and place theory supported by the existence of primary and secondary use interweaved by cultural events exemplified by the actions in urban space. The direct and participant observation technique is employed, supplemented by maps and photographs to record the inquiry persuasively. It is learned that the accessibility of the user from all directions (connected by short cut path), the diverse activities at every corner of the blocks of shophouses, the continuous flow of the primary and secondary use intertwine in between the main street and lanes support the connectivity of urban linkage in the area. Finally, the urban phenomenon is distinguished from the intertwines of the street user, activities, and physical aspects as well as surrounding buildings with different functions that rendered the happening through the urban scene.